Analisa Pengukuran Cylinder Liner dan Piston pada Overhoul Diesel Engine - Lilin Hermawati; Iman Mujiarto; Sugeng Hariyadi; Kundori (Accurate: Journal of Mechanical Engineering and Science, 2020)
In addition to knowing the various types of machining components that exist, operators are required to know the maintenance and be able to measure each component so that the diesel engine's performance does not experience problems that result in decreased engine performance. Meanwhile, the supporting components of the diesel engine are like cylinder liners, because the cylinder liner components determine the volume of the cylinder and the performance of the diesel engine. The shape of the cylinder liner is like a tube where the manufacturing process uses a horizontal centrifugal casting process. Horizontal Centrifugal casting process is a casting process for making cylinder liners by pouring molten metal into a rotating mold. Implementation of Top Overhaul on diesel engines is carried out by opening the cylinder head or the top of the engine. The parts examined include the rocker arm, inlet and exhaust valves, injectors, air starting valves and push rods. Top Overhaul is carried out when the working hours of the diesel engine have worked with around 6,000 hours of work. Major Overhaul maintenance, which includes inspection, maintenance and inspection carried out on all Top Overhaul works and on the piston, connecting rod, piston ring, seated metal and road metal. Major Overhaul maintenance is carried out when the diesel engine has 12,000 working hours according to the Diesel Engine Intruction Book. In the cylinder liner often occurs damage or looseness which is commonly referred to as abrasion, erosion and corrosion. Because of that the cylinder liner requires maintenance and measurement using an inside micrometer tool. From the results of the measurements and maintenance on the cylinder liner, the calculation of the consistency, taper and wear was obtained, to find out the specifications or exceed the limits specified in the Main Engine Intruction Book on the ship.